Intra-arterial angiolymphoid hyperplasia with eosinophilia of the temporal artery: Report of two cases and review of the literature - Hao-Tien Hsiao; Yu-Hung Wu (Wolters Kluwer Medknow Publications, 2012)
Angiolymphoid hyperplasia with eosinophilia (ALHE) is a relatively common benign vascular disorder of uncertain etiology and has many synonyms, such as pseudopyogenic granuloma, atypical pyogenic granuloma, epithelioid hemangioma, and histiocytoid hemangioma. It usually develops on the head and neck, manifesting as reddish-to-dark purpuric papules or nodules. In this article, we report two patients who had uncommon intra-arterial ALHE that occurred in the temporal artery. In both cases, the ALHE presented as skin-colored subcutaneous nodules over the forehead, mimicking temporal arteritis. Histopathologically, intravascular epithelioid endothelial cell proliferation occurred, with lymphocyte and eosinophil infiltration in the stroma. One patient also showed typical findings of ALHE in the adjacent soft tissue. We know of seven similar cases that have previously been reported in the literature to date.